Implementation of the Sciencepreneur Approach through Project-Based Learning in Making Natural Shampoo to Improve Critical Thinking Skills of SD UMP Students in the 2024/2025 Academic Year - Latifah Dwi Utami; Ristiana Dyah Purwandari (UM Purwokerto Press, 2025)
This study aims to examine the implementation of the Sciencepreneur approach through project-based learning in making natural shampoo to improve the critical thinking skills of fourth-grade students at SD UMP in the 2024/2025 academic year. 21st-century education demands an innovative and interdisciplinary learning process that integrates science concepts with entrepreneurship to develop students' critical thinking and entrepreneurial skills. The research method used is quantitative with a pre-test and post-test design involving 28 students. Project-based learning requires students to actively work in groups through stages of literacy, production, packaging, and promotion of environmentally friendly and healthy natural shampoo products, as an alternative to commercial products containing harmful substances and associated with socio-political issues. The results show a significant improvement in students’ critical thinking abilities, with the class average score increasing from 60 in the pre-test to 92.124 in the post-test, and the percentage of students passing the Minimum Competency Criteria (KKM) rising from 35.7% to 100%. These findings support the hypothesis that the implementation of the Sciencepreneur approach in project-based learning effectively improves students’ critical thinking skills. It is recommended that future research assess the product evaluation and its utilization through promotion on social media and school activities.